Art and modernism in socialist China : unexplored international encounters, 1949-1979 - Kong, Shuyu; Andrews, Julia Frances; Zheng, Sheng Tian, 1938-; Global Art Exchange and Modernism in Socialist China 1949-1979 (Workshop) (2020 : Simon Fraser University) (New York, NY : Routledge, 2024)
"This edited volume will be the first book examining the art history of China's socialist period from the perspective of modernism, modernity, and global interactions. The majority of chapters are based on newly available archival materials and fresh critical frameworks/concepts. By shifting the frame of interpretation from socialist realism to socialist modernity, this study reveals the plurality of the historical process of developing modernity in China, the autonomy of artistic agency, and the complexity of an art world conditioned, yet not completely confined, by its surrounding political and ideological apparatus. The unexpected global exchanges examined by many of the authors in this study and the divergent approaches, topics, and genres they present add new sources and insights to this research field, revealing an art history that is heterogeneous, pluralistic and multi-layered. The book will be of interest to scholars working in art history, art and politics, and Chinese studies"--
Chile, China, Cuba : a mural and beyond / Shengtian Zheng -- Tan Huamu's pictorial diaries in the era of the new China / Tao Cai -- The Romanian oil painting training class and modernist undercurrents in Chinese art : education of the socialist period / Juliane Noth.
Outgrowth of the workshop "Global Art Exchange and Modernism in Socialist China 1949-1979" hosted by David Lam Centre at Simon Fraser University in October 2020.
Keywords: Art and globalization -- China -- History -- 20th century; Art and society -- China -- History -- 20th century; Modernism (Art) -- China; Socialism and art -- China; ART / History / General; ART / Asian; ART / Art & Politics